Longitudinal Development of Receptive Vocabulary in Children with Cerebral Palsy and Anarthria: Use of the MacArthur-Bates CDI. (3rd July 2020) - Molinaro, Michael; Broman, Aimee Teo; Rathouz, Paul J.; Hustad, Katherine C.
ABSTRACT: Objective: To examine receptive language growth in children with cerebral palsy (CP) and anarthria using a parent-reported measure of vocabulary. Method: Scores from 47 children (29 males) with CP and anarthria were obtained from the vocabulary checklists on the MacArthur-Bates Communication Development Inventories (MCDI) and analyzed to examine the distribution of receptive language growth. Linear trajectories of word composite scores were created using a linear-mixed model, incorporating between two and ten data points per child. Results: Three different growth trajectories emerged: approximately 23% grew by 100 or more words per year, 13% grew by 50–100 words per year, and 64% grew by 50 words per year or less. Age-four vocabulary was strongly correlated with rate of increase in vocabulary. Conclusion: Receptive vocabulary scores from the MCDI are increasing at a reduced pace for most children with CP and anarthria. More sensitive measures of language assessment are necessary to gain a complete picture of their language ability levels.